Urban population density and mortality in a compact Dutch city: 23-year follow-up of the Dutch GLOBE study. (September 2018) - Beenackers, Mariëlle A.; Oude Groeniger, Joost; Kamphuis, Carlijn B.M.; Van Lenthe, Frank J.
Abstract: We investigated the association and underlying pathways between urban population density and mortality in a compact mid-sized university city in the Netherlands. Baseline data from the GLOBE cohort study (N = 10, 120 residents of Eindhoven) were linked to mortality after 23 years of follow up and analyzed in multilevel models. Higher population density was modestly related to increased mortality, independently of baseline socioeconomic position and health. Higher population density was related to more active transport, more perceived urban stress and smoking. Increased active transport suppressed the mortality-increasing impact of higher population density. Overall, in dense cities with good infrastructure for walking and cycling, high population density may negatively impact mortality. Highlights: Higher population density is modestly related to higher mortality in a dense Dutch city. High population density is associated with more active transport. High density levels are associated with more perceived urban stress and smoking. Active transport suppresses the mortality-increasing impact of higher density.